Pengembangan Desain Produk Tas Kuliah Yang Efisien Bagi Mahasiswa Desain Di Stikom Surabaya - Darwin Yuwono Riyanto; Hardman Budiarjo; Faisal Fuadi Mahmud (CandraRupa : Journal of Art, Design, and Media, 2019)
One of the facilities that are needed in the world of lectures is a bag, because the bag is used by students to store goods or to carry equipment and student needs. various types and models of bags on the market that can be an option for students. But the bag model that is most popular with students is the backpack model. Because the backpack model college backpack can store all the needs and equipment for college. For college study program design students who have to be brought in very many and varied, including drawing books, drawing paper (A3) drawing tools, stationery, laptops, lecture books. So it is not uncommon for students to carry 2 bags namely college bags and picture pipe bags. This causes inefficiency for students in carrying bags. Therefore arises the idea of the writer to design an efficient college bag design for design students at Stikom Surabaya. So the concept of this design is to streamline the college bag that can carry all the equipment and lecture needs for design study students.